Debt and structural adjustment programmes: the effects on women in Africa - Etim, Ekei (Technical Centre for Agricultural and Rural Cooperation, 1993)
Dr Ekei U Etim is a Research Officer with the Council for World Mission. Apart from her work as a part-time Lecturer at the University of London she belongs to organizations such as the Institute for African Alternative, Akina Mama Wa Afrika and the...